Antiplasmodial Activity of Some Medicinal Plants Used in Sudanese Folk-medicine - El-Hadi M. Ahmed; Bakri Y.M. Nour; Yousif G. Mohammed; Hassan s. Khalid (SAGE Publishing, 2010)
Ten plants indigenous to Sudan and of common use in Sudanese folk-medicine, were examined in vitro for antimalarial activity against schizonts maturation of Plasmodium falciparum , the major human malaria parasite. All plant samples displayed various antiplasmodial activity. Three plant extracts caused 100% inhibition of the parasite growth at concentrations of plant material ≤ 500 ug/ml. The two most active extracts that produced 100% inhibition of the parasite growth at concentration of plant material ≥ 50 μg/ml were obtained from the seeds of Nigella sativa and the whole plant of Aristolochia bracteolata. The ten plants were phytochemically screened for their active constituents. The two most active plants showed the presence of sterols, alkaloids and tannins.